Неорганические соединения хрома: Справочник - Рябин В. А. Виктор Афанасьевич; Киреева М. В. Мария Валерьяновна; Берг Н. А. Нина Андреевна; Житкова Т. Н. Тамара Николаевна; Леонтьева И. А. Инесса Ароновна; Калитина Л. Н. Лидия Николаевна; Устьянцева Т. А. Тамара Анатольевна (Ленинград, Химия, 1981)
Сост. указаны на обороте тит. л.